Analysis on Earnings Persistence, Independent Commissioner and Herding Behavior on Earnings Quality - Ike Arisanti (JABE (JOURNAL OF ACCOUNTING AND BUSINESS EDUCATION), 2019)
This study aims at determining the effect of independent commissioners, earnings persistence, and herding behavior on earnings quality. This study employs a multiple linear regression analysis with SPSS as the statistical tool. Before conducting the hypothesis test, a classical assumption test is conducted first, determining whether the data have met the classical assumptions and may be applied to the regression model. There are four components used in the classical assumption test, namely normality test, multicollinearity test, heteroscedasticity test, and autocorrelation test. This study takes 80 qualified manufacturing companies listed with the Indonesia Stock Exchange in 2017 as the object with a purposive sampling technique. The earnings quality variable is measured using ERC, the Herding behavior is measured using Cross Sectional Absolute Deviation (CSAD), the Independent Commissioners are measured by comparing the number of independent commissioners with overall commissioners in the companies, and the earnings persistence is measured by comparing current earnings with past earnings. The results of this study partially show that earnings persistence variable, independent commissioners and herding behavior do not influence the quality of earnings.